Case Report: Multiple autoimmune syndrome (MAS)—An unusual combination - Kwong, Elaine Yi Lee; Kuok, Manson Chon In; Chan, Winnie Kwai-Yu (Frontiers in Pediatrics, 2022)
This is a case report of a Chinese adolescent boy who had multiple autoimmune syndrome (MAS) of a rare combination comprising type 1 diabetes, Hashimoto thyroiditis and childhood-onset systemic lupus erythematosus (SLE). He developed SLE within one year of symptom onset, presenting with necrotising histiocytic lymphadenitis and hepatitis. We highlight the importance for physicians to be aware of the need for continued surveillance for developing new autoimmune diseases in patients with multiple autoimmune diseases. It is also essential to remain vigilant for overlap syndrome as autoimmune diseases commonly share similar subphenotypes and non-specific autoantibodies. Long-term follow-up is warranted to define the final phenotype.